PERSEPSI IBU AKSEPTOR KB TENTANG METODE AMENOREA LAKTASI DENGAN ASI EKSKLUSIF DI LINGKUNGAN IV KELURAHAN MEDAN SUNGGAL MEDAN TAHUN 2016 - Nopita Yanti Sitorus (Universitas Negeri Medan, 2017)
ABSTRACT Perception is a process that involves the entry of messages or information into the human brain. One of the contraceptives that can be used after delivery is Lactation Amenorrhea Method (MAL) that is contraception that relies exclusively on breastfeeding, meaning that with this method menstruation does not appear regularly for 24 weeks or 6 months 10% will have menstrual 10 weeks post salin, 20% At 20 weeks, 60% at 30 weeks. This research was conducted to know the perceptions of mother of KB acceptor about method of amenorrhoea lactation with exclusive breastfeeding in environment VI of Dwikora sub district of Medan. Data collection is done based on primary data and secondary data. Primary data in this research is questionnaire (questionnaire), while secondary data in this research is by using method of documentation. So the population obtained in this study as many as 80 people and the number of samples as many as 80 people using total sampling. This type of research is descriptive correlational. The data were analyzed by univariate and bivariate analysis using Chi square or square ki (X2). The results showed that the perceptions of mother of KB acceptor about method of amenorrhea lactation mostly enough that is 52 people (65%). Exclusive breastfeeding most of the failed ie 52 people (65%). From the result of statistical analysis obtained p value 0,00 (<0,05) which means there is significant correlation between perceptions of mother acceptor of KB about method of amenorrhoea lactation with exclusive breastfeeding in environment VI dwikora village of Medan. The conclusion of this research shows that statistic analysis obtained p value 0,00 (<0,05) meaning that there is significant correlation between perception of mother of KB acceptor about lactation amenorrhea method with exclusive breast feeding in iv kelurahan medan sunggal Medan Kata Kunci: Persepsi, Lactation Amenorrhea Method, Exclusive Breast Milk